A new species of the genus Archiboreoiulus Brolemann, 1921 (Diplopoda, Julida) from Movile Cave (Southern Dobrogea, Romania) - Giurginca, Andrei; Vănoaica, Liviu; Šustr, Vladimir; Tajovský, Karel (Zootaxa, 2020)
Up to the present, the genus Archiboreoiulus included only two species: A. sollaudi from France and A. pallidus with a wide European distribution range. Here we describe a previously unknown species of the genus Archiboreoiulus, A. serbansarbui, collected from the mesothermal sulfurous Movile Cave, Mangalia, Romania, harboring a rich and diverse troglobitic community.